A Narrativa do herói: um mito chamado Naruto - Silva, Francisco Alves da (2019)
The present study discusses the process of constitution of the hero from the analysis of anime Naruto. Based on studies by Campbell (1997), Luyten (2011), Yin (2015), among others, we see how anime and manga show themselves as exponents of Japanese pop culture and how it relates to the Brazilian consumer market. Thus, we see the media force in the diffusion of Japanese cultural products and how it builds an identity, building new imaginary relationships in the western daily lives of children and young people. For the construction of this project, we propose to rely on the bibliographic method and case study to understand the transformation of a character created under an oriental mythological bias becomes universal and commercial. From the point of view of creativity, Panofsky (1982) helps us understand the creative strategies in the conception of the Japanese pop hero and identify the marks of this discourse in the characters of the Naruto series. In the present study, we made a comparative analysis through the trajectory of the protagonist of the series with the mythological association of the Nine-Tailed Fox. It is concluded that the strict relationship between consumer and product within the Japanese pop culture should be deepened for a better understanding of the phenomenon, considering its considerable socio-cultural importance in the Brazilian reality.